Особливості росту та розвитку Paeonia tenuifolia L. на північній межі Лісостепу України - Gnatiuk, A.M.; Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to analyze the peculiarities of ontomorphogenesis P. tenuifolia on the northern border of the Forest-Steppe of Ukraine, to establish diagnostic signs of age stages and the sequence of their passage in M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Material and methods. We studied P. tenuifolia in artificially created phytocoenoses and culture. Observations were conduct for 5 years (from 2013 to 2018). We studied ontomorphogenesis by generally accepted methods. Results. Diagnostic features of age stages of individuals in latent, pregenerative, generative and senile periods of ontogenesis are established. Detailed morphological descriptions of plants in different age stages and the sequence of their passing by individuals are shown. Conclusions. The peculiarities of the growth and development of P. tenuifolia on the northern border of the Ukrainian Forest-Steppe are manifested in the multivariate ontomorphogenesis. Established that is difficult to distinguish the immature plants from the subsenile ones on the aboveground part of plants only. In the reproductive period is not possible to determine a degree disintegration of the rhizome and calculate the number of individuals. Estimating the age range in populations (both natural and artificial), it is only possible to identify the number of aboveground shoots of different age states and the presence of generative reproduction in plants. P. tenuifolia can be grown in the culture and artificially created phytocoenoses of the on the northern border of Forest-Steppe of Ukraine.